MASALAH PEMAHAMAN COVID-19 DAN TUGAS FILSAFAT - Mikhael Dua (Institut Filsafat dan Teknologi Kreatif Ledalero, 2021)
Public understanding of Covid 19 is often seen as a source of problems in pandemic time. This article presents a discussion that the logic of understanding is different from the logic of explanation. If in scientific explanation, law and scientific theory are regarded as the premises, all human understanding departs from the historical experience of the world which belongs to the community. In a phenomenological perspective, human understanding is rational because it is oriented toward convergence without coincidence, unification without equivalence, commonality without identity, and cooperation without uniformity. The Study of the musical experiences of East Nusa Tenggara shows that the people of East Nusa Tenggara have a transverse rationality, in a sense that is convergent with the health protocol, although is based on the mythical cosmology. Based on this kind of logos, any effort in solving Covid 19's problem as a point of convergence needs interpretation of local community different understanding.Key words: Covid 19, Edmund Husserl, Phenomenology, rationality, transversality.